2015
DOI: 10.1016/j.pscychresns.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of ketamine on glutamate-glutamine and gamma-aminobutyric acid in obsessive-compulsive disorder: Proof of concept

Abstract: We previously reported the rapid and robust clinical effects of ketamine versus saline infusions in a proof-of-concept crossover trial in unmedicated adults with obsessive-compulsive disorder (OCD). This study examined the concurrent neurochemical effects of ketamine versus saline infusions using proton magnetic resonance spectroscopy (1H MRS) during the clinical proof-of-concept crossover trial. Levels of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) and the excitatory neurochemicals glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…Gonadal hormones, such as estrogen and progesterone, may also potentiate the rapidity and potency of ketamine’s antidepressant effects, as demonstrated in preclinical models (Carrier and Kabbaj, 2013; Franceschelli et al, 2015; Hashimoto, 2016). Lastly, ketamine interaction with GABA receptors has been implicated in various clinical pathologies, including obsessive-compulsive disorder (Rodriguez et al, 2015), depression (Perrine et al, 2014) and learning disabilities following chronic exposure (Tan et al, 2011). …”
Section: Proposed Mechanisms Of Actionsmentioning
confidence: 99%
“…Gonadal hormones, such as estrogen and progesterone, may also potentiate the rapidity and potency of ketamine’s antidepressant effects, as demonstrated in preclinical models (Carrier and Kabbaj, 2013; Franceschelli et al, 2015; Hashimoto, 2016). Lastly, ketamine interaction with GABA receptors has been implicated in various clinical pathologies, including obsessive-compulsive disorder (Rodriguez et al, 2015), depression (Perrine et al, 2014) and learning disabilities following chronic exposure (Tan et al, 2011). …”
Section: Proposed Mechanisms Of Actionsmentioning
confidence: 99%
“…Previous studies suggest that ketamine increases glutamatergic transmission and alters excitatory/inhibitory balance within the mPFC 45,46,47 . However, our baseline photometry recordings ( Figure 1) indicated that KO animals had increased fronto-striatal activity compared to WT animals during grooming, leading us to hypothesize that the therapeutic effect of ketamine might be associated with decreasing activity in this projection to resemble WT activity patterns during grooming.…”
Section: Ketamine Selectively Increases In Vivo Fronto-striatal Projementioning
confidence: 98%
“…Ketamine (Ketalar), a voltage-dependent, non-competitive and non-selective N-methyl-D-aspartate (NMDA) receptor antagonist, acts by inhibiting the fluidity of calcium and sodium cations in the presence of glutamate and glycine (Niciu, Henter, Luckenbaugh, Zarate, Jr., & Charney, 2014). In adults with OCD, ketamine infusions appear to normalize low GABA levels in medial prefrontal cortex (Rodriguez et al, 2015). While ketamine has shown utility in the treatment of refractory depression (Iadarola et al, 2015), only case reports are available for the use of ketamine in OCD.…”
Section: Psychopharmacologymentioning
confidence: 99%